Common Imaging Mistakes and Pitfalls of the Elbow: Focus on Pediatrics and Young Adults - Fanney, Lewis; Yaya-Quezada, Carlos; Nguyen, Ngan P.; Yang, David L.; Gendler, Liya; Zoga, Adam C.; Nguyen, Jie C. (Seminars in Musculoskeletal Radiology, 2025)
This review covers physiologic changes that occur with normal elbow development, imaging considerations, and common elbow pathologies, subdivided into those involving the medial, lateral, and posterior compartments. At the medial elbow, medial epicondylar apophysitis and avulsion factures are more common among skeletally immature individuals, whereas ulnar collateral ligament injuries are more common among skeletally mature young adults. At the lateral elbow, radial head subluxation, capitellar osteochondritis dissecans, and Panner's disease are more common among skeletally immature individuals. At the posterior elbow, olecranon physeal stress injury is more common among skeletally immature individuals, whereas triceps tendon injury is more common among skeletally mature individuals. We also highlight pathologies in and around the elbow joint, including septic arthritis, juvenile idiopathic arthritis, rheumatoid arthritis, and osteoid osteoma.
Keywords: elbow; OCD; magnetic resonance imaging; pediatrics; stress injury